O transístor e os vaga-lumes: deslocamentos, territórios e sociabilidade literária na produção tardia e no panteão-portátil de Murilo Mendes - Elaine Amélia Martins (2021)
This thesis examines the late poetic experiments of Murilo Mendes, whose sample are the poems of the first part of Convergência (1970) and the poetic prose of the anthology Transístor (1980), the relationship of the poet-critic with his own time, with his experience of displacement and his transit between tradition and modernity. We seek to understand the double topos of the trip as a trigger for the changing of the poet's writing record and, above all, for the construction of his greatest artistic and political project put into practice in his last production, that is, the creation and maintenance of a community – of his portable pantheon – and his insertion in it. For this purpose, the relationship between poetry and technique or literature and technology is approached, elaborating the notions of technological transistor (technical device) and poetic transistor (poetic device). The poetic transistor term is transformed here into an operational concept to read the Murilian work and is still linked to the portable, to ideas of resistance and to the image of the fireflies survival, in Georges Didi-Huberman terms. The notion of late production, the late in literature, is treated, as well as those of territory in Murilian poetic prose, printing the writer's desire for archiving and his movement towards the Republic of Letters. The central concepts of precursors, intercessors, collection, inheritance and paideuma are also covered. It is intended to collaborate to think about the place of the deterritorialized/reterritorialized poet in the literary and artistic field inherent to his craft, reading the literature as a collective enterprise and a territory of sociability.